Design, synthesis and investigating the interaction of novel s-triazine collector with pyrite surface : a DFT-D3+U and experimental studies - Mkhonto, Peace P.; Zhang, Xingrong; Lu, Liang; Xiong, Wei; Zhu, Yangge; Han, Long; Ngoepe, Phuti E. (Elsevier, 2023)
In this study the green (environmentally friendly) novel di-sodium 2,6-dithio-4-butyl-amino-1,3,5-Triazine (SDTBAT) collector also known as s-triazine molecule was designed and synthesised for use in sulphide minerals separation. The SDTBAT adsorption was investigated on pyrite mineral surface using computational density functional theory with dispersion correction and U-parameter (DFT-D3+U) as well as experimental methods. The chemical adsorption behaviour of SDTBAT collector was compared with the sodium normal butyl xanthate (SNBX) and sodium normal butyl dithiocarbamate (SNBDTC). Computationally, it was observed that the SDTBAT adsorbed through the S and N atoms, while SNBX and SBDTC adsorbed through S atoms onto pyrite Fe atoms. The adsorption energies followed the decreasing adsorption strength as: SDTBAT > SNBX > SNBDTC, which suggested that the SDTBAT had strong exothermic adsorption than xanthate and DTC. The experimental microflotation tests showed fast floating and higher recoveries of pyrite when using the SDTBAT collector compared to xanthate and DTC. The XPS and FTIR analysis of pyrite-SDTBAT revealed that the SDTBAT adsorbed through S and N atoms on Fe atoms. This clearly demonstrated that the SDTBAT was a potential collector to replace the xanthate collector due to its high flotation power for separation of sulphide minerals.
Journal article published in the journal of Surfaces and Interfaces 38 (2023) 102820
Keywords: DFT-D3+U-Pyrite surface; Micro-flotation; s-Triazine; Adsorption-dispersion energies; Electronic properties; XPS-FTIR analysis; Heptazine; Sulfide minerals; Electronic apparatus and appliances -- Thermal properties; Flotation